2004
DOI: 10.1172/jci200419140
|View full text |Cite
|
Sign up to set email alerts
|

Extensive tissue-regenerative capacity of neonatal human keratinocyte stem cells and their progeny

Abstract: Given our recent discovery that it is possible to separate human epidermal stem cells of the skin from their more committed progeny (i.e., transit-amplifying cells and early differentiating cells) using FACS techniques, we sought to determine the comparative tissue regeneration ability of these keratinocyte progenitors. We demonstrate that the ability to regenerate a fully stratified epidermis with appropriate spatial and temporal expression of differentiation markers in a short-term in vitro organotypic cultu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

16
112
0
4

Year Published

2004
2004
2014
2014

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 153 publications
(133 citation statements)
references
References 44 publications
16
112
0
4
Order By: Relevance
“…These layers of epidermis are the major contributors to tissue repair, as they have the highest proliferative capacity (63) and, therefore, can be considered as primary targets for proinflammatory molecules. Interestingly, we found that Ca 2ϩ -induced differentiation of cultured HEK leads to decreased production of cortisol (data not shown).…”
Section: Discussionmentioning
confidence: 99%
“…These layers of epidermis are the major contributors to tissue repair, as they have the highest proliferative capacity (63) and, therefore, can be considered as primary targets for proinflammatory molecules. Interestingly, we found that Ca 2ϩ -induced differentiation of cultured HEK leads to decreased production of cortisol (data not shown).…”
Section: Discussionmentioning
confidence: 99%
“…Despite the significant progress made in this area, reliable identification criteria to distinguish between stem and nonstem epidermal cells are still lacking. [30][31][32] Thus, the use of nonintegrative vectors such as adenoviruses or the inclusion of adjustable excisional elements 25 would be safer.…”
Section: Transient Improvement Of a Local Situationmentioning
confidence: 99%
“…Experimental evidence supporting this idea was demonstrated in the conditional ability of early differentiating human keratinocytes to regenerate a stable stratified epidermis when supported by inductive dermal cells and supplemented with extracellular matrix proteins (34). When highly-inductive dermal papilla cells were implanted into split footpad skin in contact with the basement membrane, cultured dermal papilla cells could induce HF morphogenesis and hair growth in adult epidermis (35) suggesting that signals derived from fully inductive dermal papilla cells can re-program most proliferative keratinocyte populations irrespective of their previous lineage commitment.…”
Section: Epidermal Plasticity and The Skin Microenvironmentmentioning
confidence: 96%